Liver stiffness measurement predicts long‐term survival and complications in non‐alcoholic fatty liver disease. (8th December 2019) - Shili‐Masmoudi, Sarah; Wong, Grace Lai‐Hung; Hiriart, Jean‐Baptiste; Liu, Ken; Chermak, Faiza; Shu, Sally She‐Ting; Foucher, Juliette; Tse, Yee‐Kit; Bernard, Pierre‐Henri; Yip, Terry Cheuk‐Fung; Merrouche, Wassil; Chan, Henry Lik‐Yuen; et al.
Abstract: Background and aims: In non‐alcoholic fatty liver disease (NAFLD), fibrosis is the strongest prognostic factor and can be assessed by non‐invasive methods. We evaluated the ability of liver stiffness measurement (LSM) to predict overall survival and liver, cardiovascular and oncologic complications. Methods: We prospectively collected data on 2251 consecutive NAFLD patients (mean age 59 years, male 53%, mean body mass index 28 kg/m 2 ) in two centres. At inclusion, all patients had LSM, clinical and biological evaluation. During follow‐up, we recorded cardiovascular events, cancers, liver complications, liver transplantation and death. The primary endpoint was overall survival. Survival curves according to LSM were first performed using Kaplan‐Meier method for the primary endpoint, and Aalen‐Johansen method for secondary outcomes to take into account competitive risks. In a second step, a Cox proportional hazard model analysis was done to identify independent predictors of overall survival. Results: Median follow‐up was 27 months [IQR: 25‐38]. Fifty‐five patients died and three patients had liver transplantation. Overall survival significantly decreased as baseline LSM increased. Twenty‐one patients (0.9%) had a liver event, 142 (6.3%) developed cancer (excluding HCC) and 151 (6.7%) had a cardiovascular event during follow‐up. By multivariable analysis, independent predictors of overall survival were as follows: baseline LSM (adjusted HR (aHR) = 2.85 [1.65‐4.92], P  = .0002), age (aHR = 1.11 [1.08‐1.13], P  < .0001) and male sex (aHR = 2.05 [1.17‐3.57], P  = .012). Patients with elevated LSM were also more likely to develop cardiovascular, and liver events but not other cancers. Conclusion: LSM can be used to predict survival, cardiovascular and liver complications in NAFLD patients.